Communicating through a Scandal: The Case Study of Japan LDP’s Ties with the Unification Church - Anisa Ledy Umoro (IZUMI, 2024)
The existing literature on political scandals predominantly focuses on their detrimental effects on society at large. This paper aims to offer an alternative perspective, arguing that political scandals can lead to positive change. It does so by examining the case of Japan’s ruling party, the Liberal Democratic Party (LDP) and its ties to the controversial religious organization, the Unification Church (UC). These ties were brought into public attention, following the assassination of the former Japanese Prime Minister, Shinzo Abe. Drawing on the framework of scandal mediation process (Prusa, 2010), this paper defines scandal as a form of communication between the elite and the masses, that facilitated by the media. By consulting data from newspapers and government reports, this paper investigates the progression of the scandal. It highlights how the communication unfolded during the progression of the scandal through public pressure, intense media coverage, public apologies by members of the political elites, and attempts to mitigate the damage. Moreover, this paper argues that the swift response from the government, notably the passing of anti-malicious donation law, shows that a political scandal can positively impact the functioning of social order. Focusing on how and under what circumstance a political scandal may have a positive impact introduces a richer nuance to the discussion of Japanese political scandals as demonstrated by these findings. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor